Pterostilbene and treadmill exercise induce white adipose browning in rats - ZHENG Jiawei; LIU Wujian; ZHU Jundong; MI Mantian (Di-san junyi daxue xuebao, 2020)
Objective To investigate the effects of pterostilbene (PST) intervention and treadmill exercise on browning of white adipose in rats and explore the molecular mechanisms. Methods Twenty-four 8-week-old male SD rats were randomly divided into 4 groups: sedentary control group (C), 50 mg/kg PST treatment group, treadmill exercise (EX) group, and treadmill exercise with PST treatment (EX+PST) group. After corresponding treatments for 4 consecutive weeks, the rats were evaluated for changes in food intake, body weight and inguinal white adipose tissue (iWAT) mass. The morphological features of the iWAT were analyzed with HE staining. The mRNA and protein levels of the marker genes and the regulatory molecules for white fat browning in the iWAT were determined using real-time quantitative PCR and Western blotting, respectively. Results The body weight gain and iWAT index in the 3 treatment groups were all significantly lower than those of the control group (P < 0.05), while food intake did not differ significantly among the 4 groups. Compared with those in the control group, the adipocytes within the iWAT in the 3 treatment groups showed a smaller size and a more spherical morphology accompanied by the presence of cellular compartmentation, which were all characteristics of brown adipocytes. The mRNA and protein levels of the marker genes and regulatory molecules for white adipose browning, including uncoupling protein 1 (UCP1), cell death-inducing DNA fragmentation factor alpha-like effector A (CIDEA), cluster of differentiation 137 (CD137), transmembrane protein 26 (TMEM26), carnitine palmitoyltransferase 1A (CPT1A), cytochrome c (Cyto c), silent information regulator 1 (Sirt1), peroxisome proliferator activator receptor gamma coactivator 1 alpha (PGC-1α), PR domain-containing 16 (PRDM16) and phosphorylated adenosine monophosphate activated protein kinase (p-AMPK) were all significantly increased in the iWAT in the 3 treatment groups (P < 0.05). These changes were more obvious in EX+PST group than in EX group and PST group (P < 0.05). Conclusion PST intervention and treadmill exercise, either alone or in combination, can induce the browning of iWAT and reduce fat accumulation and body weight gain in rats through a mechanism possibly involving the activation of AMPK signal transduction pathway. PST combined with treadmill exercise produces more pronounced effects than either PST or treadmill exercise alone